Distribution of anti-nuclear antibodies (ANA), anti-dsdna and extractable nuclear antigens (ENA) antibodies among apparently healthy malay women and determination of ana cutofftitre - Che Maraina, Che Hussin (Pusat Pengajian Sains Perubatan, 2013)
Distribution of anti-nuclear antibodies (ANA), anti-dsDNA and extractable nuclear antigens (ENA) antibodies among apparently healthy Malay women and determination of ANA cut-off titre. Previous studies discovered that autoantibodies were present in healthy people at various dilutions. Some autoantibodies play a very important role in the pathogenesis, diagnosis and prognosis of autoimmune diseases including antinuclear antibodies (ANA), antidsDNA and ENA antibodies. In diagnostic procedures, establishing a cut-off value that can discriminate between healthy and diseased people is very important to reduce false positive results. Therefore, this study aimed to determine the cut-off titre for ANA test, the distributions of ANA, anti-dsDNA and ENA antibodies among apparently healthy Malay women and the seroconversion of ANA positivity after 6, 12 and 18 months in this cohort. This study was divided into two phases. Phase I was designed as a case-control study that involved a group of 59 SLE patients as cases and 101 healthy women as controls at childbearing age. Medical records review was used to obtain ANA results of the patients. Healthy women were recruited from HUSM based on the inclusion and exclusion criteria. Phase 2 was designed as a prospective cohort study and was a continued evaluation of healthy women for their ANA, anti-dsDNA and ENA antibodies levels. The blood was tested for ANA and anti-dsDNA antibodies using immunofluorescence method that used HEp-2 cells and Crithidia luciliae as the substrate, respectively. The current cut-off titres for ANA and anti-dsDNA antibodies tests are :0:1:40 and <:I :10, respectively. ENA antibodies were determined based on the principle of an enzyme immunoassay. Twelve antigens coated on a strip were tested. A sample was considered positive for a specilic antibody if the colour intensity of the corresponding antigen dot was higher than the intensity of the negative control dot. Data entry and analysis were done using Predictive Analytics SoftWare (PASW) Statistics 18. Receiver operating characteristics (ROC) curve was plotted in StataSE 9 for determination of ANA cut-offtitre. In healthy women aged 20 to 40 years, the prevalence of ANA positive and ENA positive were 3.0% (0, 6.0) and 5.0% (0.6, 9.4) respectively. Three subjects had positive ANA composed of one positive subject at the highest dilution I :40 and two subjects at 1:80. All 0 Division of Research & Innovation- Universiti Sains Malaysia -20130118 positive subjects displayed speckled pattern. No positivity of anti-dsDNA antibodies was found in all the subjects. For ENA antibodies test, one subject was positive for RNP antigen, three subjects for SSA antigen and one subject for PM-Scl antigen. However, these five positive subjects were found to be ANA-negative. The follow-up on ANA seroconversion at 6-month, 12-month and IS-month period found three subjects with circulating ANA in their bloodstream which occurred at fluctuating dilutions. Eleven subjects had detectable ANA at least once. The highest dilution of ANA was detected at l :80. Based on the ROC curve, the cut-off titre for ANA was chosen at I :80 with 97.4% sensitivity and 83.5% specificity. In conclusion, the prevalence of ANA in healthy Malay women at this population was comparatively low as compared to other studies. Anti-dsDNA antibodies were not detected, which explained the significance of these antibodies as a specific diagnostic marker for SLE. This study also discovered the positivity of ENA antibodies in five negative-ANA subjects. There was insufficient information to conclude the significance of this event in non-symptomatic subjects. The fluctuations of ANA positivity in healthy women over 2-year period occurred mainly below the level of the current cut-off titre, l :40. The cut-off titre for ANA was determined at I :80.